Academic Supervision of Madrasah Heads and Supervisors for PAI Cluster Teachers at State MTs throughout Boyolali Regency in 2022/2023 - Suprihatin, Suprihatin (AS-SABIQUN, 2023)
This study aims to analyze the supervision carried out by madrasa heads and supervisors in order to maximize the potential of PAI subject teachers in MTs throughout Boyolali Regency. This study used a qualitative approach with a survey method using a questionnaire. This research was conducted at MTs N in Boyolali Regency, Central Java. The research instrument used in this study was a questionnaire. The subjects of this study were all school principals, school supervisors and teachers at MTs Negeri throughout the district. The technique of collecting data by distributing questionnaires is related to the academic supervision of madrasah heads and supervisors of Islamic Religious Education teachers at MTs N throughout Boyolali. Data analysis techniques are data reduction, data display and verification. The results of this study are the supervision of the madrasa head in assisting teachers in planning and implementing learning, assisting in analyzing students' needs in learning and assisting teachers in overcoming difficulties in implementing learning. while the supervision of supervisors of supervising madrasas is to provide consulting services to teachers individually or in groups to improve the learning process from the teacher and the learning outcomes. The impact on teacher performance is to increase the competency and professionalism of Islamic education teachers in MTs N throughout Boyolali Regency.